Effects of Zinc Oxide Nanoparticles Synthesized Using Aspergillus niger on Carbapenem-Resistant Klebsiella pneumonia In Vitro and In Vivo - Rasha, Elsayim; Alkhulaifi, Manal M.; AlOthman, Monerah; Khalid, Ibrahim; Doaa, Elnagar; Alaa, Khatab; Awad, Manal A.; Abdalla, Mohnad (Frontiers in Cellular and Infection Microbiology, 2021)
Currently, the mortality rate is increasing in Saudi Arabia's ICU, due to the spread of KPC. This project was carried out to evaluate the ability of the biological synthesized of zinc Oxide nanoparticles (ZnO-NPs) using Aspergillus niger to overcome Carbapenem-Resistant Klebsiella pneumonia (KPC) in vitro and in vivo. ZnO-NPs was synthesized via a biological method and characterized using UV-Vis spectroscopy, Zeta sizer and Zeta potential analyses, X-ray diffraction (XRD) spectroscopy, Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX). In vitro sensitivity of KPC to ZnO-NPs was identified using the well diffusion method, MIC and MBC was determined by macro dilution method. The morphological alteration of KPC cell after ZnO-NPs treatment was showed by SEM. In vivo susceptibility of KPC to ZnO-NPs ointment was evaluated using wound healing in experimental rats. The chemical characterization findings showed the formation, stability, shape and size of the synthesized nanoparticles. The MIC and MBC results was found in 0.7mgand 1.8mgrespectively. in vivo results displayed the inflammation reduction and wound healing re-epithelialisation of kpc infected rats. these findings demonstrated that ZnO-NPs has great potential to be developed as antibacterial agents and wound healing.